2009
DOI: 10.1111/j.1365-3059.2008.01904.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced expression of sucrose synthase and alcohol dehydrogenase I genes in phytoplasma‐infected grapevine plants grown in the field

Abstract: Interaction between phytoplasma and grapevine at the physiological level is still poorly understood, as are plant defence mechanisms against the pathogen. This study investigates the level of gene expression of three selected genes in a large number of grapevine plants belonging to six disease/cultivar groups (healthy Chardonnay, Bois noir-infected Chardonnay, Flavescence dorée-infected Barbera and Prosecco, and recovered Barbera and Prosecco). All plants were grown in vineyards in uncontrolled conditions in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…We have previously shown that an accurate classification of plants as uninfected or infected with 'Ca. P. solani' is also possible with other tools, for example with a support vector machines algorithm (Hren et al 2009b). Although the results of such classification have been confirmed to be very accurate, they are without real applied value because the analysis is very laborious, requiring RT-qPCR analysis of 17 genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that an accurate classification of plants as uninfected or infected with 'Ca. P. solani' is also possible with other tools, for example with a support vector machines algorithm (Hren et al 2009b). Although the results of such classification have been confirmed to be very accurate, they are without real applied value because the analysis is very laborious, requiring RT-qPCR analysis of 17 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen abundance was assessed (Table 1) in the same samples as were collected for evaluation of host plant gene expression to ensure that phytoplasma was alive and active at the time of sampling. The expression of Stol11cDNAwas normalized to expression of COX and 18S rDNA reference genes and relatively quantified as previously described in detail (Hren et al 2009b). For the relative quantification, plant 24 was used as a calibration sample.…”
Section: Pathogen Abundancementioning
confidence: 99%
See 2 more Smart Citations
“…The most common symptoms of the infected plants are yellowing caused by the breakdown of chlorophyll and carotenoids, whose biosynthesis is also inhibited (21). Induced expression of sucrose synthase and alcohol dehydrogenase I genes in phytoplasma-infected grapevine plants grown in the field was also recently demonstrated (72).…”
Section: Relevant Features Of Phytoplasmasmentioning
confidence: 99%